Protein Palmitoylation in Leukocyte Signaling and Function - Yang, Xiaoyuan; Chatterjee, Victor; Ma, Yonggang; Zheng, Ethan; Yuan, Sarah Y. (Frontiers in Cell and Developmental Biology, 2020)
Palmitoylation is a post-translational modification (PTM) based on thioester-linkage between palmitic acid and the cysteine residue of a protein. This covalent attachment of palmitate is reversibly and dynamically regulated by two opposing sets of enzymes: palmitoyl acyltransferases containing a zinc finger aspartate-histidine-histidine-cysteine motif (PAT-DHHCs) and thioesterases. The reversible nature of palmitoylation enables fine-tuned regulation of protein conformation, stability, and ability to interact with other proteins. More importantly, the proper function of many surface receptors and signaling proteins requires palmitoylation-meditated partitioning into lipid rafts. A growing number of leukocyte proteins have been reported to undergo palmitoylation, including cytokine/chemokine receptors, adhesion molecules, pattern recognition receptors, scavenger receptors, T cell co-receptors, transmembrane adaptor proteins, and signaling effectors including the Src family of protein kinases. This review provides the latest findings of palmitoylated proteins in leukocytes and focuses on the functional impact of palmitoylation in leukocyte function related to adhesion, transmigration, chemotaxis, phagocytosis, pathogen recognition, signaling activation, cytotoxicity, and cytokine production.